Can Preterm Labour Be Predicted in Low Risk Pregnancies? Role of Clinical, Sonographic, and Biochemical Markers. (22nd October 2014) - Tripathi, Reva; Tyagi, Shakun; Singh, Nilanchali; Mala, Yedla Manikya; Singh, Chanchal; Bhalla, Preena; Ramji, Siddhartha
Abstract : Background and Objectives. This is a prospective nested cohort study conducted over a period of 3 years. 2644 women were recruited, out of which final analysis was done for 1884 women. Methods . Cervicovaginal and blood samples were collected for all recruited women. Out of these, 137 women who delivered before 35 weeks were treated as cases and equal number of matched controls were chosen. Analysis of samples for serum G-CSF, AFP, ferritin, and cervicovaginal interleukin-6 and IGFBP-1 was done. Results . Poor orodental hygiene, which can be a social marker, was significantly more common in women who delivered preterm (P = 0.008 ). Serum alkaline phosphatase and serum ferritin were found to be significantly associated with preterm deliveries. The 90th percentile value of these parameters was considered as cut-off as there is no specific cut-off. Conclusions . Our study did not prove usefulness of any predictive marker. Serum ferritin and alkaline phosphatase were found to have correlation but their values are affected in many conditions and need to be elucidated with caution. Larger studies are needed for predicting preterm labour in asymptomatic women.